On Inspecting the Hierarchical Inter-Relationships amongst Benefits and Challenges Faced by Decentralised Finance as well as Fiscal Decentralisation - Jauhar, Jyotin; Aggarwal, Remica (Contemporary Research in Business, Management and Economics Vol. 3, 2024)
Decentralized finance [DeFi] uses a combination of existing block chain-related technologies — such as digital assets, wallets, smart contracts and auxiliary services including Oracles. Common services offered by DeFi platforms include payments, loans, trades, investments, insurance and asset management. Present research work discusses the benefits and challenges faced by decentralized finance. This also further explores the hierarchical inter-relationships amongst them using ISM methodology. It further discusses about Fiscal decentralization.